CORPORATE SOCIAL RESPONSIBILITY AND OWNERSHIP STRUCTURE: ANALYSING THE IMPACT OF MANDATORY CSR (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
While extant scholarship examining the  relationship between Corporate Social  Responsibility (CSR) and ownership structure,  no work has examined how Mandatory  CSR impacts the CSR-Ownership structure  nexus. Coercive pressure from law plays a  crucial role in influencing how the ownership  structure of companies can affect the CSR  performance. Accordingly, it is crucial to  understand the difference between CSR and  ownership structure relationship before and  after the implementation of Section-135  of the Companies Act, 2013 in the Indian  context. In the present study, we draw on  institutional theory to explore if the corporate  sector responds to institutional pressures. Our  analysis of a sample of NIFTY 100 index firms  for the period 2010-2019 illustrates that the  impact of ownership structure on CSR is higher  in the period after the implementation of  mandate. Our theoretical arguments and results  emphasize the value of multiple perspectives to  evaluate the impact of Mandatory CSR on the  link between CSR and ownership structure.
Keywords: Corporate Social Responsibility; Ownership Structure; Agency Theory; Institutional Theory; NIFTY 100; Panel Data